Scrutinizing university students’ online learning readiness and learning achievement - Ismail, Ismail; Syukri, Syukri; Sukmawati, Ati (Pegem Journal of Education and Instruction, 2022)
This study aims to determine the level of student online learning readiness (OLR) and determine its correlation with students’ learning achievement (LA). To achieve this goal, a mixed-method with a correlation design was applied. The data was taken by administering OLR questionnaire, holding interview, and documenting students’ final scores in Islamic philosophy courses. This score in this study was considered as students’ LA. 56 first-semester students from a public university in West Nusa Tenggara, Indonesia became the participants. The results showed that the majority of students were ready with improvement for joining online learning (OL) as indicated by the average OLR score of 3.65. However, students mentioned some challenges during OL such as unstable internet connection, unconducive learning environment, and inability to be a multitasker. This study revealed that students’ OLR had a very strong correlation to LA as shown by r=0.085, sig=0.000. Henceforth, this study implied the need for teachers and educational institutions to help students to be ready to join the new learning system. However, this study promotes improvement for future investigation because of its limited variables and samples.